Cross compatibility in intraspecific and interspecific hybridization in yam (Dioscorea spp.) - Mondo, J.; Agre, A.P.; Edemodu, A.; Asiedu, R.; Akoroda, M.O.; Asfaw, A. (Springer, 2022)
Yam (Dioscorea spp.) is a staple crop for millions of people in the tropics and subtropics. Its genetic improvement through breeding is being challenged by pre-zygotic and post-zygotic cross-compatibility barriers within and among species. Studies dissecting hybridization barriers on yam for improving the crossability rates are limited. This study aimed to assess the cross-compatibility, which yielded fruit set, viable seeds and progeny plants in an extensive intraspecific and interspecific crossing combinations in a yam genetic improvement effort to understand the internal and exogenous factors influencing pollination success. Cross-compatability was analyzed at the individual genotype or family level using historical data from crossing blocks and seedling nurseries from 2010 to 2020 at the International Institute of Tropical Agriculture (IITA). The average crossability rate (ACR) was lower in interspecific crossing combinations (6.1%) than intraspecific ones (27.6%). The seed production efficiency (SPE) values were 1.1 and 9.3% for interspecific and intraspecific crosses, respectively. Weather conditions and pollinator's skills are the main contributors to the low success rate in the intraspecific cross combinations in yam breeding. At the same time, genetic distance and heterozygosity played little role. Interspecific cross barriers were both pre-zygotic and post-zygotic, resulting from the evolutionary divergence among the yam species. Dioscorea rotundata had higher interspecific cross-compatibility indices than D. alata. Distant parents produced intraspecific crossbred seeds with higher germination rates compared to closest parents (r = 0.21, p = 0.033). This work provided important insights into interspecific and intraspecific cross-compatibility in yam and suggested actions for improving hybridization practices in yam breeding programs.